Three Complementary One‐Pot Four‐Component Reaction Sequences for Rapid, General and Direct Spiropyran Synthesis. Issue 2 (8th December 2022) - Hughes‐Whiffing, Christopher A.; Perry, Alexis
Abstract: Three one‐pot three‐step four‐component reaction sequences for spiropyran synthesis have been developed, based around three different methods for in situ generation of 1, 2, 3‐trisubstituted indoles (indole N ‐alkylation, Fischer indolisation and indole C ‐alkylation). The reaction sequences give access to a broad swathe of spiropyran structures. Each sequence is operationally straightforward, rapid and high yielding. We have synthesized 58 structurally diverse spiropyrans bearing a wide range of useful functional groups, and their utility were demonstrated in the targeted synthesis of potential ratiometric fluorescence probes for metal ions and spiropyran‐cholesterol conjugates. Finally, we showed that our one‐pot N ‐alkylation‐ C ‐alkylation‐condensation sequence can underpin combinatorial spiropyran synthesis through generation of a 16‐member spiropyran library. Abstract : Three distinct one‐pot three‐step four‐component processes for spiropyran synthesis were developed. These complementary reaction sequences enable efficient and straightforward synthesis of structurally diverse spiropyrans from simple and readily available precursors.